Reliability and performance analysis of safety-critical system using transformation of UML into state space models - Mamdikar M.R.; Kumar V.; Singh P.; Singh L. (My University, 2025)
Non-functional requirement analysis is the most critical factor for safety-critical system construction as it reduces the risk of catastrophic loss of assets by taking measurable actions in the design phase. Reliability and performance analysis are the two main components of non-functional requirement analysis. In this paper, a reliability analysis framework is devised, which maps the Unified Modeling Language (UML) state chart model into the state-space model to analyze dynamic behavior and state transition probabilities of a safety-critical system. A system that does not meet the target reliability and performance requirements is considered to be a failure. The proposed framework is validated with 32 safety-critical system instances of the Nuclear Power Plant on the Reactor Core Isolation Cooling System module. © 2020 Elsevier Ltd